Photoelectrochemical performance of P@MoS2 for hydrogen evolution reaction - Thurga Devi, Munusamy; Khan, Maksudur R.; Chin, Sim Yee (Elsevier Ltd, 2021)
Hydrogen production through water splitting could be a splendid technique as an alternative to fossil fuel derived methods. Recently, molybdenum disulfide (MoS2) has gained great attention for electrocatalytic HER. Nevertheless, the catalytic activity of MoS2 was limited by poor active sites with higher intrinsic activity. The present work correlates the enhancement on the performance of MoS2 was done by doping with phosphorus that contribute for the higher activity of hydrogen evolution reaction (HER). During light irradiation, the phosphorus doped MoS2 (P@MoS2) possessed lowest overpotential (134 mV) and smallest Tafel slope (86 mV/dec) in contrast to bulk MoS2 thereby propitious for HER activities. Thus, the highly effective P@MoS2 nanocomposite could be a remarkable candidate that reassuring the growth of hydrogen production regimes.